PENGARUH WOM DAN SMME TERHADAP WTP FITUR TAMBAHAN PADA APLIKASI MOBILE GAME FREEMIUM DENGAN MEDIASI CBI - Soesilo, Primidya Kartika Miranda; Prayogo, Riswoyo Ponco; Talumewo, Vanny Vanessa; Purnomo, Wiseno Adi (2021)
The willingness of customers to pay for additional features of the mobile freemium games is an interesting benchmark to research. The purpose of this study is to investigate the influence of social media activities, such as e-WOM (electronic Word of Mouth) and or Social Media Marketing Effort (SMME) on Willingness To Pay (WTP), with special consideration of the role Consumer Brand Identification. It was found that SMME was not able to influence consumers in Indonesia to feel close to the brand, this happened because customers used the game's social media only to find one-way information and tutorials, and they preferred to interact directly with other gamers through the features in the game (e.g chat), and the customer prioritizes the entertainment and fun elements created from the interaction between these gamers. Further interviews with respondents also found that e-WOM is able to create deeper relationships for customers with the brand of the game they are playing, because customers often tell other gamers good things about the game when they interact each other, and they become endorser for the game which make they consistently connected with the brand. The analytical method used in this research is Particle Least Square Structural Equation Model (PLS SEM)